Anticancer Activity of Ferulic Acid-Inorganic Nanohybrids Synthesized via Two Different Hybridization Routes, Reconstruction and Exfoliation-Reassembly - Hyoung-Jun Kim; Kitae Ryu; Joo-Hee Kang; Ae-Jin Choi; Tae-il Kim; Jae-Min Oh (The Scientific World Journal)
We have successfully prepared nanohybrids of biofunctional ferulic acid and layered double hydroxide nanomaterials through reconstruction and exfoliation-reassembly routes. From X-ray diffraction and infrared spectroscopy, both nanohybrids were determined to incorporate ferulic acid molecules in anionic form. Micrsocopic results showed that the nanohybrids had average particle size of 150 nm with plate-like morphology. As the two nanohybridization routes involved crystal disorder and random stacking of layers, the nanohybrids showed slight alteration in z-axis crystallinity and particle size. The zeta potential values of pristine and nanohybrids in deionized water were determined to be positive, while those in cell culture media shifted to negative values. According to the in vitro anticancer activity test on human cervical cancer HeLa cells, it was revealed that nanohybrids showed twice anticancer activity compared with ferulic acid itself. Therefore we could conclude that the nanohybrids of ferulic acid and layered double hydroxide had cellular delivery property of intercalated molecules on cancer cell lines.